Youth Labour Market Performance in Spain and its Determinants A Micro-Level Perspective - Dolado, Juan J.. (OECD Economics Department Working Papers, 2013)
This paper provides both descriptive and empirical evidence about the main youth labour market problems in Spain. Using the experiences of other EU economies as a benchmark, we document the performance of Spain as regards a wide set of youth labour market dimensions. These include employment and unemployment rates, youth wages, decisions to work and study, youth mobility, type of employment contract, time to find a first job, skill mismatch, etc. Cross-country econometric evidence from different micro-datasets is reported to understand the role played by several underlying supply/demand factors which might explain the difficulties faced by the Spanish youth labour market (www.oecd.org/eco/surveys/Spain)